(untitled) (Metallurgy and Foundry Engineering, 2017)
Aluminium and aluminium alloys are now widely used as materials for structural applications due to a number of valuable properties. Improvement in functional and decorative properties of aluminium can be obtained by forming an oxide layer on its surface. The aim of the present study was to produce and compare the properties of oxide layers on the surface of aluminium alloy 7075 and compare their properties. Methods which were used during the study were as follows: phosphating, micro-arc oxidation, and a chemical method involving the formation of the passive layer. Layers were subjected to corrosion tests. SEM and EDS methods were used for characterization of received results. Also some tests on optical ptofilometer were done. It was proven that the micro-arc oxidation method allows for obtaining a layer with the greatest thickness and highest corrosion resistance.